IMPLEMENTASI KURIKULUM MERDEKA BELAJAR PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SMK PUSAT KEUNGGULAN SMK MUHAMMADIYAH SINTANG - Muharrom Muharrom; Aslan Aslan; Jaelani Jaelani (CV. ADIBA ASIHA AMIRA, 2023)
The independent learning curriculum is structured as a complement to the previous curriculum with a more active and flexible learning approach and frees teachers and students to carry out the learning process based on religious values, Pancasila and the nation's culture. In this regard, the Central Government has given authority to each Central Vocational School of Excellence to develop and implement a learner-centered independent learning curriculum. The focus of this research is (1) How is the planning of learning Islamic religious education in the Independent Learning Curriculum at the SMK Muhammadiyah Sintang Excellence Center? (2) How is the implementation of Islamic religious education learning in the Independent Learning Curriculum at the Central Vocational High School of Muhammadiyah Sintang Vocational School? and (3) How is the evaluation of Islamic religious education learning in the Independent Learning Curriculum at the Central Vocational High School of Muhammadiyah Sintang Vocational School?. This research method uses descriptive qualitative. The techniques used in data collection are observation, interviews and documentation. Techniques in data collection are multiple sources of evidence (data triangulation), data reduction, data presentation and drawing conclusions and verification. Research findings (1) PAI teacher learning planning in the Independent Learning Curriculum; attending training, compiling teaching tools, making teaching materials in accordance with the Pancasila Student Profile, adjusting learning methods and strategies and preparing media, tools and learning resources (2) Implementation of PAI teacher learning in the Merdeka Learning Curriculum is to use the MERRDEKA flow approach which is applied in initial activities, core activities and final or closing activities (3) Evaluation of PAI teacher learning in the Independent Learning Curriculum is to use a summative and formative evaluation model in the form of oral tests, products and projects